PREMATURE BIRTH PROBLEM IN MODERN STAGE OF MEDICAL SCIENCE DEVELOPMENT. Part 1 - E. S. Sakharova (Rossijskij Vestnik Perinatologii i Pediatrii, 2017)
Improving the health status of the population at the moment is a global problem widely discussed at the highest level in all regions of the globe. The main tasks of the international health-care organizations are to develop a strategy aimed at increasing the level of health and life expectancy, in particular, by reducing the infant morbidity and mortality, as well as finding the best tactics for nursing the infant in case of premature birth.The data presented in the article demonstrate the variety of risk factors and mechanisms of early birth, social, economic, medical, genetic factors affecting the course of pregnancy and childbirth are covered, modern variants for the classification of prematurity and the dynamics of data of Russian and foreign statistics on the tendency of infant mortality rates are given, frequency of premature birth and survivability of premature infants is discussed in detail.The main objective of the study of these factors is the development of preventive (prophylactic) measures in relation to prematurity, the introduction of modern technologies to predict, prevent and adequately manage premature births to reduce infant morbidity, and to find the optimal tactics for nursing a child in the event of premature birth.